An open coding analytical model of sermons on poverty with Matthew 25:31-46 as sermon text - H. J. C. Pieterse (Acta Theologica)
This article reports on the first cycle (out of three) of a grounded theory analysis of sermons on poverty with Matthew 25:31-46 as sermon text. The problem addressed in this research project has to do with the poverty situation in South Africa. The leading research question is: how do preachers deal with sermons on poverty with this text as sermon text. The goal of the first phase in this project is to develop an open coding analytical model from the sermons. Six sermons by Uniting Reformed Church preachers and six sermons by Dutch Reformed Church preachers have been analyzed. Significant sermon segments in the light of the research question were then coded in the analysis. Initial categories could then be formed as they emerged from the data, based on the open coded codes. From the categories an open coding analytical model with hypotheses has been constructed.